The New PEGASUS-III Experiment - Sontag, Aaron C.; Bongard, Michael W.; Borchardt, Michael T.; Diem, Stephanie J.; Fonck, Raymond J.; Keyhani, Armand K.; Kujak-Ford, Benjamin A.; Lewicki, Benjamin T.; Nornberg, Mark D.; Palmer, Alan C.; Pierren, Christopher; Reusch, Joshua A.; et al. (IEEE transactions on plasma science, 2022)
Developing attractive means of initiating current without using magnetic induction from a central solenoid is a critical scientific and technical challenge facing the spherical tokamak (ST). The PEGASUS program has focused on developing the physics basis and predictive models for nonsolenoidal tokamak startup using local helicity injection (LHI) and has demonstrated startup to ~0.2 MA in a low-field, near-unity aspect ratio ( A ) ST. The PEGASUS facility is being upgraded into a solenoid-free ST called PEGASUS-III. Major features include: increased toroidal field (TF) to 0.6 T for up to 100 ms, improved shape control, and retaining the low-aspect ratio geometry of A \sim 1.2 . This TF directly supports the new mission to expand the breadth of solenoid-free research on the facility with multiple reactor-relevant techniques. The implemented TF upgrade is comprised of a new center rod, outer TF coil system, torque plate assemblies, and TF interconnects between the center rod and outer conductors. The center rod is comprised of 24 water-cooled, insulated wedge conductors inside a new inner vacuum wall. There is no ohmic solenoid, which allows additional TF conductor for the 48-kA/turn TF current. The outer TF conductors are 12 pairs of air-cooled, reinforced Al plate conductors. Pairwise crossed conductor links connect the outer C-plates to the central rod conductor to eliminate the need for a toroidal compensation wind-back coil. Torque plate assemblies on top and bottom mechanically secure both the outer C-conductor and the interconnecting links, counteract torsional magnetic loads during a pulse, and provide compliance for vertical displacement. The assembly accommodates magnetic and thermal forces, limiting the axial excursion of the central assembly to <1 mm.